2017
DOI: 10.1371/journal.pone.0177512
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary transition towards permanent chloroplasts? - Division of kleptochloroplasts in starved cells of two species of Dinophysis (Dinophyceae)

Abstract: Species within the marine toxic dinoflagellate genus Dinophysis are phagotrophic organisms that exploit chloroplasts (kleptochloroplasts) from other protists to perform photosynthesis. Dinophysis spp. acquire the kleptochloroplasts from the ciliate Mesodinium rubrum, which in turn acquires the chloroplasts from a unique clade of cryptophytes. Dinophysis spp. digest the prey nuclei and all other cell organelles upon ingestion (except the kleptochloroplasts) and they are therefore believed to constantly acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Overall, results in this study highlight the different photosynthetic behavior in Teleaulax and Mesodinium relative to Dinophysis species, despite the fact that the latter seem to maintain some control over their kleptoplasts (Hansen et al 2016, Rusterholz et al 2017. In that sense, the only genetic clue so far to explain this observation has been the discovery of five proteins with photosynthetic function encoded in the nuclear genome of D. acuminata (Wisecaver and Hackett 2010).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Overall, results in this study highlight the different photosynthetic behavior in Teleaulax and Mesodinium relative to Dinophysis species, despite the fact that the latter seem to maintain some control over their kleptoplasts (Hansen et al 2016, Rusterholz et al 2017. In that sense, the only genetic clue so far to explain this observation has been the discovery of five proteins with photosynthetic function encoded in the nuclear genome of D. acuminata (Wisecaver and Hackett 2010).…”
Section: Discussionmentioning
confidence: 60%
“…, Rusterholz et al. ). In that sense, the only genetic clue so far to explain this observation has been the discovery of five proteins with photosynthetic function encoded in the nuclear genome of D. acuminata (Wisecaver and Hackett ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability for kleptochloroplast maintenance lowers the need for frequent ingestion and a recent study even reported division of kleptochloroplasts in Dinophysis spp. (Rusterholz et al 2017). Photoacclimation, as proven in Mesodinium (Moeller et al 2011), also decreases photo-oxidative stress on chloroplasts and makes them last longer.…”
Section: Gncm and Sncmmentioning
confidence: 98%
“…This view is supported by observations of a gradual decline of the photosynthetic performance in old kleptoplastids relative to that of the newly acquired in well-fed cells [55]. Recently, Rusterholz et al [56] rejected the "dilution" theory and suggested a certain capacity of Dinophysis for kleptoplastid division, arguing in favour of a greater control than previously thought. In any case, starved condition led to a decline in kleptoplastid numbers per cell.…”
Section: Uptake Rates Of Well-fed Versus Starved Cells Of Dinophysismentioning
confidence: 91%